Epitope Mapping of Streptococcus agalactiae Elongation Factor Tu Protein Recognized by Human Sera - Pyclik, Marcelina; Górska, Sabina; Brzozowska, Ewa; Dobrut, Anna; Ciekot, Jarosław; Gamian, Andrzej; Brzychczy-Włoch, Monika (Frontiers in Microbiology, 2018)
The elongation factor Tu has been identified as one of the most immunoreactive proteins that was recognized by human sera of GBS (group B streptococcus) positive patients. In this paper, we present the polypeptide-specific epitopes of the bacterial protein that are recognized by human antibodies: 28LTAAITTVLARRLP41 (peptide no. 3) and 294GQVLAKPGSINPHTKF309 (peptide no. 21). To determine the shortest amino acid sequence recognized by antibodies, truncation peptide libraries were prepared using the PEPSCAN method. The analysis of immunoreactivity of peptides with sera of GBS positive and negative women revealed that the most immunoreactive sequence was 306HTKF309. Moreover, we observed that this sequence also showed the highest specificity which was based on ratio of reactivity with sera of GBS positive relative to sera of GBS negative patients. Epitope was synthetized on Wang resin with the Fmoc strategy. Our results open the possibility to use 306HTKF309 peptide in diagnostic assays to determine Streptococcus agalactiae infection in humans.